Aspects of the granulomatous reaction in the liver of mice infected and reinfected with two different geographical strains of Schistosoma mansoni - Pedro Raso; Paulo Marcos Z. Coelho; Nivaldo H. Toppa; Rômulo T. Mello (Revista da Sociedade Brasileira de Medicina Tropical, 1994)
In this study, which was undertaken in relation to the histopathologic behavior of two different strains (LE-Belo Horizonte, MG and SJ - São José dos Campos, SP) in infections and reinfections (homologous or heterologous) with Schistosoma mansoni, the authors confirmed a more accentuated pathogenicity of the SJ strain. All the reinfections showed the presence of typical granulomas of the acute phase, when performed either with the same strain (homologous) or with a different strain (heterologous) of the parasite of the primo infection. The possible mechanisms responsible for reactivation of the immunopathologic response in reinfections are discussed.